The Harness Maker's Dream : Nathan Kallison and the Rise of South Texas - Kotz, Nick (Book collections on Project MUSE., 2013)
Both historical study and ancestral narrative, The Harness Maker's Dream follows the story of Ukrainian immigrant Nathan Kallison's journey to the United States in search of a brighter future. At the turn of the twentieth century, over two million Jews emigrated from Czarist Russia and Eastern Europe to escape anti-Semitic law. Seventeen-year-old Kallison and his brothers were among those brave enough to escape persecution and pursue a life of freedom by leaving their homeland in 1890. Faced with the challenges of learning English and earning wages as a harness maker, Kallison stru.